Storytelling Therapy Effectively Reduces Anxiety in Children with Leukemia at DR Wahidin Sudirohusodo General Hospital Makassar - Ruris Haristiani; Wahyuningsih Wahyuningsih; Susaldi Susaldi (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2022)
Background: Children with leukemia are prone to experience anxiety due to various factors. Moreover, side effects of chemotherapy such as diarrhea, nausea, and vomiting add stress to the children. Storytelling therapy can be used as one of the non-pharmacological methods to reduce anxiety in children. Objectives: seeing the effectiveness of storytelling therapy with audio-visual media in reducing anxiety in children with leukemia. Methods: quantitative research with quasi-experimental: pretest-posttest without a control group. Anxiety in children is measured by Hamilton Anxiety Rating Scale (HARS) instrument. Statistical test with the Wilcoxon signed-rank test with α = 0,05. Results: There is a decrease in anxiety levels in children with leukemia after being given story-telling therapy. Based on data analysis by the Wilcoxon test, p: 0.000 means story-telling therapy is effective in reducing anxiety in children with leukemia at RSUP DR Wahidin Sudiro Husodo Hospital Makassar. Conclusion: Storytelling therapy with audio-visual media is effective in reducing anxiety levels in children with leukemia.